Effect of Patient Compliance With Treatment Recommendations on Clinical Outcomes in Chronic mTBI: A TEAM-TBI Study. Issue 7 (16th March 2020) - Galey, Jessica L; Eagle, Shawn R; Blaney, Nicholas A; Holland, Cynthia L; Bitzer, Hannah B; Schneider, Walt; Okonkwo, David O; Mucha, Anne; Collins, Michael W; Kontos, Anthony P
Abstract: Introduction: Treatment approaches for mild traumatic brain injury (mTBI) have evolved to focus on active and targeted therapies, but the effect of compliance with therapy has not been investigated. The purpose of this study was to examine the role of patient compliance with prescribed therapies on clinical outcomes following mTBI. Materials and Methods: Participants were aged 18-60 years with chronic (ie, 6+ months) mTBI symptoms who were previously recalcitrant ( n  = 66). Participants were diagnosed with a vestibular disorder and were prescribed vestibular and exertion therapies. Participants were instructed to continue the exercise regimen during the 6-month treatment phase at home. Participant compliance was evaluated by clinicians at patients' follow up visit as: (1) high, (2) moderate, or (3) low compliance based on patient report and clinician interview. High-compliance was compared to a combined low- and moderate-compliance group on the outcomes using a 2 (group) × 2 (time) analysis of variance. Results: 39 of the 66 (59%) participants with vestibular disorder returned for a 6-month evaluation and were included in the analyses. Of these 39 participants, 16 (41%) were high-compliance (36.7 ± 10.9 years, 18.8% female), 17 (44%) were moderate-compliance (32.5 ± 5.5 years, 23.5% female), and 6 (15%) were low-compliance (32.7 ± 3.3 years, 0% female). Conclusion: High compliance significantly reduced total Vestibular/Ocular Motor Screening scores compared to low/middle compliance ( P  = .005). Post-Concussion Symptom Scale was reduced by 48% and dizziness symptoms reduced by 31% in the high-compliance cohort. High compliance with prescribed exertion/vestibular rehabilitation therapies enhanced clinical outcomes for previously recalcitrant patients with chronic mTBI-related vestibular disorders.